Risk Factors for Grade 3 to Grade 4 Adverse Reactions to the ChAdOx1 nCoV-19 Vaccine (AZD1222) Against SARS-CoV-2 - Lee, Sang Won; Lee, Hyun; Lee, Sun-Kyung; Moon, Ji-Yong; Moon, SeolHwa; Chung, Sung Jun; Yeo, Yoomi; Park, Tai Sun; Won Park, Dong; Kim, Tae-Hyung; Sohn, Jang Won; Yoon, Ho Joo; et al. (Frontiers in Medicine, 2021)
Objective Limited data are available regarding the rates and risk factors of severe to serious adverse reactions (ARs) to the ChAdOx1 nCoV-19 vaccine. Methods Eligible participants were healthcare workers who received their first dose of the ChAdOx1 nCoV-19 vaccine in either of two university hospitals in Seoul, Korea. We evaluated the type and severity of ARs seven days after the first dose of the ChAdOx1 nCoV-19 vaccine using a questionnaire survey delivered via a smartphone application link. Results Among the 1,603 participants who completed the survey, 684 (42.7%) participants experienced any kind of grade 3 to grade 4 AR. Being young (adjusted odds ratio [OR] for age 21–30 years = 2.49, 95% confidence interval [CI] = 1.75–3.56; adjusted OR for 31–40 years = 1.78, 95% CI = 1.22–2.62; adjusted OR for 41–50 years = 1.47, 95% CI = 1.03–2.11), being female (adjusted OR = 2.16. 95% CI = 1.62–2.89), and being underweight (adjusted OR = 1.61, 95% CI = 1.02–2.55) were identified as risk factors for grade 3 to grade 4 ARs. Among comorbidities, only diabetes mellitus (adjusted OR = 2.36, 95% CI = 1.03–5.53) was identified as a risk factor. When stratified by the type of AR, being young and being female were risk factors for both local and systemic grade 3 to grade 4 ARs. Conclusions Being young, female, or underweight and having diabetes mellitus were associated with an increased risk of developing grade 3 to grade 4 ARs after receiving the first dose of the ChAdOx1 nCoV-19 vaccine.